Homoeopathic Management of Allergic Rhinitis using Pulsatilla Nigricans –A Case report - Dr. Vani Oza; Dr. Ankit Dubey (The Bioscan, 2025)
A 36-year-old woman presented to the outpatient department on 12/04/2024 with complaints of recurrent rhinorrhea and occasional cough of allergic origin. She was diagnosed with allergic rhinitis by the physician. The patient was treated with homoeopathic management for six months and showed considerable improvement. Improvement was also observed on the Japanese Rhinoconjunctivitis Quality of Life Questionnaire (JRQLQ). KEYWORDS Allergic Rhinitis, case report, Homoeopathic Treatment, Pulsatilla Nigricans.